Archives of Agronomy and Soil Science - Archives of Agronomy and Soil Science (Taylor & Francis, 2026)
Archives of Agronomy and Soil Science is a well-established journal that has been in publication for over fifty years. The Journal publishes papers over the entire range of agronomy and soil science. Manuscripts involved in developing and testing hypotheses to understand casual relationships in the following areas: plant nutrition; fertilizers; manure; soil tillage; soil biotechnology and ecophysiology; amelioration; irrigation and drainage; plant production on arable and grass land; agroclimatology; landscape formation and environmental management in rural regions; management of natural and created wetland ecosystems; bio-geochemical processes; soil-plant-microbe interactions and rhizosphere processes; soil morphology, classification, monitoring, heterogeneity and scales; reuse of waste waters and biosolids of agri-industrial origin in soil are especially encouraged.
FI 0.58
Q1
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Ciencia del suelo; Agronomía; Fertilidad del suelo; Nutrición vegetal; Manejo agrícola; Procesos biogeoquímicos